Scientific Method in Late-Antique Paganism: The (Rational) Empiricism of al-Filāḥa l-nabaṭiyya (The Nabatean Agriculture) - Dalen, Elaine van (Arabica, 2021)
The reputation of the late-antique or early Islamic al-Filāḥa l-nabaṭiyya (The Nabatean Agriculture) as an esoteric forgery has recently begun to shift and its value as a source for the study of early-Islamic or late-antique Near Eastern paganism has been restored. This article contributes to a further reinterpretation of the work by elucidating its value for the history of late-antique and early Islamic science. It argues that the work distinguishes between the epistemological categories of the rational and the marvelous and critically approaches both based on a rational empiricism which it shares with contemporary disciplines such as medicine and astrology. The concepts of experience (taǧriba) and reason (qiyās) are central to al-Filāḥa l-nabaṭiyya’s epistemology, and the work relies on observation and experiments, combined with methods of deductive and analogical reasoning to obtain applied botanical and agricultural knowledge. Al-Filāḥa l-nabaṭiyya also contains competing views regarding prophecy and astrological knowledge which are illustrative of epistemological debates within Pagan late-antique scholarship.